Cortical Stimulation Induces Excitatory Postsynaptic Potentials of Inferior Colliculus Neurons in a Frequency-Specific Manner - Qi, Jiyao; Zhang, Zizhen; He, Na; Liu, Xiuping; Zhang, Caseng; Yan, Jun (Frontiers in Neural Circuits, 2020)
Corticofugal modulation of auditory responses in subcortical nuclei has been extensively studied whereas corticofugal synaptic transmission must still be characterized. This study examined postsynaptic potentials of the corticocollicular system, ie., the projections from the primary auditory cortex (AI) to the central nucleus of the inferior colliculus (ICc) of the midbrain, in anesthetized C57 mice. We used focal electrical stimulation at the microampere level to activate the AI (ESAI) and in vivo whole-cell current-clamp to record the membrane potentials of ICc neurons. ESAI-evoked changes in the membrane potentials were successfully recorded in 42 ICc neurons. We found that the ESAI induced inhibitory postsynaptic potentials in 6 out of 42 ICc neurons but only when the stimulus current was 96 µA or higher. In the remaining 36 ICc neurons, excitatory postsynaptic potentials (EPSPs) were induced at a much lower stimulus current. The 36 ICc neurons exhibiting EPSPs were categorized into physiologically matched neurons when the best frequency of the stimulated AI and recorded ICc neurons were similar (≤ 1 kHz) and unmatched neurons when they were different (> 1 kHz). Compared to unmatched neurons, matched neurons exhibited a significantly lower threshold of evoking noticeable EPSP, greater EPSP amplitude, and shorter EPSP latency. Our data allows us to propose that corticocollicular synaptic transmission is primarily excitatory and that synaptic efficacy is dependent on the relationship of the frequency tunings between AI and ICc neurons.